Insecticide resistance management of leafrollers (LepidopteraTortricidae) in New Zealand - Lo, P.; Walker, J.T.S.; Suckling, D.M. (New Zealand Plant Protection, 2000)
Resistance to the organophosphate insecticide azinphosmethyl has been previously identified in two species of leafroller (Lepidoptera Tortricidae) in New Zealand This study confirmed resistance in a third speciesCtenopseustis obliquana Populations of Epiphyas postvittana Planotortrix octo and C obliquana resistant to azinphosmethyl were not crossresistant to lufenuron A separate population of C obliquana was resistant to taufluvalinate Crossresistance between azinphosmethyl and tebufenozide occurred in P octo and C obliquana but not in E postvittana This difference in crossresistance between the three species suggests that at least two different detoxification mechanisms may be operating Therefore we cannot generalise about whether resistant populations of each species will be fully susceptible to new insecticides Lufenuron is recommended as a key insecticide within a resistance management programme for leafrollers while tebufenozide should be used with caution